Comparative measurement of customer satisfaction based on their expectation and perceived value towards Bayo service / Mohd Wahyuddin Mahmood - Mahmood, Mohd Wahyuddin (Faculty of Business and Management, 2008)
The purpose of the paper is to compare the measurement of customers' satisfaction towards Bayo service based on their expectation and perceived value by empirically based research. The research has been design by classify the precise theoretical framework. First, based on previous research, the paper builds sets of customer satisfaction instruments such as service quality, price and demographic factors. Second, the features of the service quality, price and demographic factors are identified and analyze by comparing customer expectation and their perceived value. Third, with derived instruments, the level of customer satisfaction can be measured and identifies either customers' expectation meet their perceived value or vice versa.